ANALYSIS OF THE IMPACT OF ECONOMIC AND POLITICAL INSTITUTIONS ON ECONOMIC GROWTH IN AFRICA (2012)
The importance of economic and political institutions to economic growth has been demonstrated in the literature. However, little is known on how such institutions impact on growth and what determine the quality of economic institutions in Africa. Therefore, this study was aimed at examining the impact of economic and political institutions on growth as well as the impact of political transition on the quality of economic institutions. Game theory was used to develop a political economy model that incorporated institutional variables into the neoclassical Solow growth model. This model described the interactions among political power (de-jure and de-facto powers), institutions and economic growth. The model was empirically tested using data drawn from 29 African countries covering the period 1996 to 2009. The selection of countries was guided by availability of data and they spread across the continent. Indexes of economic and political institutions were computed from the World Bank’s governance indicators and the Polity IV database. The Ordinary Least Squares (OLS), fixed effect and Generalized Methods of Moments (GMM) techniques were used to test the impact of economic and political institutions on economic growth. A treatment analysis was also employed to test the impact of political transition on the quality of economic institutions and growth. Strong economic and political institutions had significant and positive impacts on economic growth. Countries with higher institutional qualities are found to be growing faster while those with lower quality grow slower. Generally, a 1.00% increase in the indexes of economic and political institutions led to 0.44% and 0.55% increase in economic growth respectively. However, the impacts of the two indexes differed across different sub-regions. The impact of economic institutions on growth was highest in the Southern African countries with a coefficient of 0.78% and lowest in West Africa with a coefficient of 0.20%. An increase in the index of political institution had the highest impact in the Central African countries and lowest in North Africa. Specifically, political institution was found to aid growth in Central Africa by 1.19% while it slowed down growth in North Africa by 0.49%. Countries that transited to democracy recorded 1.28% improvement in their quality of economic institutions and they grew about 0.51% faster than their pre-transition era. However, for countries where political elites persisted in power after the transition, the quality of economic institutions declined by 1.10% and they experienced a lower growth rate of 0.16%. Improvement in the quality economic institutions promote growth. Competitiveness of political system improved the quality of economic institutions and growth, while elites’ persistence in power reduced the two. Economic growth in Africa can be improved by building and strengthening institutions as well as promoting competitive democracy.